Wireless Sensor Communication System with Low Power Consumption for Integration with Energy Harvesting Technology - Marsic, Vlad; Zhu, Meiling; Williams, Stewart W. (Cranfield University, 2012)
This paper reports on the design and implementation of a wireless sensor communication system with a low power consumption that allows it to be integrated with the energy harvesting technology. The system design and implementation focus on reducing the power consumption at three levels: hardware, software and data transmission. The reduction in power consumption, at hardware level in particular, is mainly achieved through the introduction of an energy-aware interface (EAI) that ensures a smart inter-correlated management of the energy flow. The resulted system satisfies the requirements of a wireless sensor structure that possesses the energy autonomous capability.